Guidance for reporting 2020 surveillance data on Transmissible Spongiform Encephalopathies (TSE). Issue 7 (2nd July 2020) - ,; Ortiz Pelaez, Angel; Papanikolaou, Alexandra; Stoicescu, Anca‐Violeta
Abstract : Thisguidanceis specifically aimed at guiding the reporting of information to EFSA under the framework of Regulation(EC) No 999/2001. The technical aspects for the reporting of surveillance data on Bovine Spongiform Encephalopathy in bovine animals, scrapieand genotyping in small ruminants (sheep and goats) and Chronic Wasting Disease in cervids are covered. The guidanceexplains the individual data elements of theStandard Sample Descriptionversion 2 (SSD2) model which are relevant for the data collection on Transmissible Spongiform Encephalopathies. Thisguidance isintended to support the reporting countries in data transmission using eXtensible Markup Language (XML) data file transfer through the Data Collection Framework according to the protocol described in the EFSA Guidance on Data Exchange version 2 (GDE2).